Characterizing the mental health and functioning of Canadian respiratory therapists during the COVID-19 pandemic. Issue 1 (31st December 2023) - D'Alessandro-Lowe, Andrea M.; Ritchie, Kimberly; Brown, Andrea; Xue, Yuanxin; Pichtikova, Mina; Altman, Max; Beech, Isaac; Millman, Heather; Levy, Yarden; Asma, Senay; Hassall, Kelly; Foster, Fatima; et al.
ABSTRACT: Introduction: Healthcare professionals (HCPs) appear to be at increased risk for negative psychological outcomes [e.g. depression, anxiety, post-traumatic stress disorder (PTSD), moral distress] and associated impacts on functioning throughout the COVID-19 pandemic. HCPs working on designated COVID-19 units may be further impacted than their colleagues not on these units given added demands of patient care and risk of contracting COVID-19. Little is known, however, about the mental health and functioning of specific professional groups beyond nurses and physicians, including respiratory therapists (RTs), over the course of the pandemic. Accordingly, the purpose of the present study was to characterize the mental health and functioning of Canadian RTs and compare profiles between RTs working on and off designated COVID-19 units. Methods: Canadian RTs completed an online survey between February and June 2021, including demographic information (e.g. age, sex, gender, ) and measures of depression, anxiety, stress, PTSD, moral distress and functional impairment. Descriptive statistics, correlation analyses and between-groups comparisons were conducted to characterize RTs and compare profiles between those on and off COVID-19 units. Results: Two hundred and eighteen ( N = 218) RTs participated in this study. The estimated response rate was relatively low (6.2%) Approximately half of the sample endorsed clinically relevant symptoms of depression (52%), anxiety (51%) and stress (54%) and one in three (33%) screened positively for potential PTSD. All symptoms correlated positively with functional impairment ( p 's < .05). RTs working on COVID-19 units reported significantly greater patient-related moral distress compared to those not on these units ( p < .05). Conclusion: Moral distress and symptoms of depression, anxiety, stress and PTSD were prevalent among Canadian RTs and were associated with functional impacts. These results must be interpreted with caution given a low response rate, yet raise concern regarding the long-term impacts of pandemic service among RTs. HIGHLIGHTS: Research on RTs' mental health prior to and during the COVID-19 pandemic is scant, especially in comparison to other HCPs. RTs in the present study reported experiencing moral distress and clinically significant symptoms of depression, anxiety and PTSD, with associated functional impairment. One in three RTs screened positive for likely PTSD on the PCL-5. There is a need to provide RTs with adequate mental health supports and to understand the long-term impacts of pandemic service among RTs.